This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Use the chain rule: ( f ( g ( x ) ) ) ′ = f ′ ( g ( x ) ) ⋅ g ′ ( x ) .
Note that lo g 2 x is just a shorthand way to write ( lo g ( x ) ) 2 , so
f ( g ) = g 2 and g ( x ) = lo g ( x )
with derivatives
f ′ ( g ) = 2 g and g ′ ( x ) = x 1 .
Putting the pieces together again, according to the chain rule, we get
f ′ ( g ( x ) ) ⋅ g ′ ( x ) = 2 g ( x ) ⋅ g ′ ( x ) = 2 ⋅ lo g ( x ) ⋅ x 1 = x 2 lo g ( x )